GIS integrated analysis of socio-environmental risk factors of dengue incidence reference to Colombo District, Sri Lanka - Swarnapali, S.B.Y.; Weerakoon, K.G.P.K. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Dengue could be considered a fast-growing vector-borne disease. The paper identifies the socioenvironmental risk factors affecting dengue incidence within dengue-prone areas and prioritizes the key risk factors to identify which highly affect incidence. Further spatial mapping of dengue-prone areas based on those factors attempts to identify dengue risk-prone areas within the study area. Data were collected through a questionnaire survey from all 57 dengue-confirmed households within the most risky Medical Officer’s Health (MOH) area in Colombo district of Western province, January-June, 2018. Eight variables were selected. Correlation and regression analysis were applied for investigating and testing the statistical significance in the relationship between socio-environmental parameters and dengue incidence. IDW interpolation technique of Geographical Information System (GIS) has been used to generate risk mapping of dengue incidence by linking the spatial points and significant socioenvironmental factors affecting incidence. The composite weight map considering all eight risk factors depicts the risk map with three risk levels (high, moderate, low). Findings shows that people should be more concerned about prevention measures against dengue and their own practices related to frequency of cleaning water storage containers in order to reduce the burden of dengue incidence.
Keywords: Dengue ncidence, confirmed dengue Cases, socio-environmental risk factors, GIS, spatial interpolation, Sri Lanka